Trial-by-trial modulations in a spatial Stroop task: A distribution analysis on social and non-social targets. - Tanaka, Yoshihiko; Oyama, Takato; Ishikawa, Kenta; Okubo, Matia (Quarterly Journal of Experimental Psychology, 2026)
In a spatial Stroop task, responses to gaze stimuli are faster when the direction and location are incongruent (reversed congruency effect), whereas responses to arrow stimuli are faster when congruent (standard congruency effect). To explain the reversal of gaze, Tanaka et al. proposed a dual-stage hypothesis comprising target–background segregation and selective inhibition. This hypothesis predicts that the enhancement of selective inhibition reduces and increases the standard and reversed congruency effects, respectively. As selective inhibition varies on a trial-by-trial basis, we tested the dual-stage hypothesis by examining congruency sequence effects (CSE) in the spatial Stroop task. We analysed the data collected from 409 participants previously tested in our laboratory. The results showed a decrease in the standard congruency effect (standard CSE) and an increase in the reversed congruency effect (reversed CSE) after incongruent trials (N − 1 incongruent) relative to congruent trials (N − 1 congruent). Reaction time distribution analysis revealed that these CSEs emerged from faster responses, suggesting that conflict monitoring in preceding trials enhanced inhibition efficiency in the current trials. These results highlighted the role of selective inhibition in the dual-stage hypothesis. Selective inhibition dynamically changes its size and onset depending on the preceding trial type and contributes to these sequential effects.